2019
DOI: 10.1177/0886260519850532
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Homelessness and Violent Victimization Among Older Adults in the HOPE HOME Study

Abstract: The homeless population is aging; older homeless adults may be at high risk of experiencing violent victimization. To examine whether homelessness is independently associated with experiencing physical and sexual abuse, we recruited 350 adults, aged 50 and older in Oakland, California, who met criteria for homelessness between July 2013 and June 2014. We interviewed participants at 6-month intervals for 3 years in Oakland about key variables, including housing status. Using generalized estimating equations, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…Subjects reporting history of violent victimization were found to be at increased risk of MDD in the present study. This result is consistent with previous findings (Mackelprang et al, 2014;Satyanarayana et al, 2015;Tong et al, 2019;Wong et al, 2016) and suggest that violent victimization should be prevented in this vulnerable population. Individuals with lived experience of homelessness face considerable marginalization, dehumanization and structural violence.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Subjects reporting history of violent victimization were found to be at increased risk of MDD in the present study. This result is consistent with previous findings (Mackelprang et al, 2014;Satyanarayana et al, 2015;Tong et al, 2019;Wong et al, 2016) and suggest that violent victimization should be prevented in this vulnerable population. Individuals with lived experience of homelessness face considerable marginalization, dehumanization and structural violence.…”
Section: Discussionsupporting
confidence: 93%
“…Individuals with lived experience of homelessness face considerable marginalization, dehumanization and structural violence. It has been shown that re-entering housing may decrease the risk of victimization (Tong et al, 2019). While some intimate partner violence survivors require extensive and possibly long-term assistance to achieve safe and stable housing (especially if they are contending with multiple complex issues), others could avoid homelessness if provided with immediate, individualized, and flexible assistance (Sullivan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…They contend with daily struggles to find shelter, food, and safety, making it difficult to focus on long-range planning. 20,21 They are less likely to attend longitudinal scheduled healthcare visits, and when they do, they are likely to have multiple concerns that require attention. These competing demands, both in daily life and within the health care visit, likely drove the recommendation to initiate ACP outside of the clinical visit, preferably until after the 13 individual obtains housing.…”
Section: Discussionmentioning
confidence: 99%
“…There may also some parallels to the literature on schizophrenia where some have argued that the onset of psychosis can be a traumatic event that leads to PTSD (Mueser et al, 2010). Further, various studies have found that homelessness is associated with high rates of death, injury, and illness (Gorman & Rowan, 2019; Nilsson et al, 2018; Riley et al, 2020; Schinka et al, 2016; Tong et al, 2019). It may also be that other PTEs are likely to occur, whereas one is homeless so that homelessness becomes a context in which one might experience a Criterion A trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In the Diagnostic and Statistical Manual of Mental Disorders‐Fifth Edition ( DSM‐5 ; American Psychiatric Association, 2013), the precipitating event or stressor is known as Criterion A and involves direct or indirect exposure to “death, threatened death, actual or threatened serious injury, or actual or threatened sexual violence.” The experience of homelessness may qualify for Criterion A as illustrated by comments made by individuals experiencing homelessness, such as “I thought I was going to die” (Law, 2019) and “My fear is being found on the street, but no one knowing how to help me or who I am” (Song et al, 2007). There are also many studies that have found homelessness is linked to substantially elevated rates of health morbidities, physical and sexual victimization, and mortality (Gorman & Rowan, 2019; Nilsson et al, 2018; Riley et al, 2020; Schinka et al, 2016; Tong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%